Wheat germ protein extraction via subcritical water for water treatment process - Daud, Nor Shazwani; Sabli, Nordin; Yoshida, Hiroyuki; Izhar, Shamsul (Tamkang University, 2025)
The attractive characteristics of subcritical water (SubCW) lie in its ability to extract and hydrolyze bioactive compounds from natural matrices. These properties allow water to act as an efficient solvent with a short extraction time. This paper aims to study the effect of SubCW temperature on wheat germ protein extraction for application in the coagulation of the water treatment process. Concerning coagulation performance, a mass-to-water ratio and extraction time are other factors studied, besides the SubCW temperature. Wheat germ (WG) is an excellent source of plant-based protein that is suitable as a biocoagulant for substituting the widely used chemical coagulants. Experiments were conducted in a batch reactor at a SubCW temperature between 100 and 170◦C with a solid-to-water ratio (s/w) of 0.5:25–2:25 and an extraction time of 5–30 min. The extracts obtained after the SubCW process contained a distinctive amount of protein, which was then used as a coagulant extract solution in the coagulation process. The highest total protein yield was 22.93 g/100 g-WG, obtained at 160◦C, which corresponds to protein extraction of 82.8%. The lowest turbidity, 48.9 NTU, was achieved at 120◦C in SubCW extracts, which resulted in a 98.8% turbidity reduction. From the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), it was observed that proteins with a molecular weight less than 117 kDa exhibit superior coagulation activity. Consequently, wheat germ protein was efficiently extracted by SubCW and can be used as a promising bio-coagulant alternative in waste treatment facilities. © The Author(’s).